The Richness of Phraseology in Poetry and Prose (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the crucial role of phraseological units in the formation of vocabulary and linguacultural competence, particularly in foreign language learning. It emphasizes that phraseology, as part of vocabulary, encapsulates a nation's cultural outlook and provides insight into how people perceive their world. The study focuses on figurative phraseological units in works of art, demonstrating how these expressions, especially in literature, reflect cultural identity and the human experience. The article also highlights the importance of phraseology in literature, both in poetry and prose, where it contributes to the richness of language, evokes emotions, and provides cultural and thematic depth.